The Utilization Of Coastal Media To Develop Symbolic Thinking Ability For 4-5 Years Old Children In Wali Urban Village, Binongko District, Wakatobi Regency - Wa Ode Ramtia; Asma Kurniati; Henny Henny (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to determine the symbolic thinking ability of chidren aged 4-5 years which includes the ability to count the number of objects from 1 to 10, recognize the concept of numbers, recognize number symbols, and recognize letter symbols. The problem in this study was that when learning observations took place, parents asked children to count the number objects from 1 to 10, recognized the concept of numbers, recognized number symbols, and recognize letter symbols and the child could already count and recognized number symbols. This research was conducted using a qualitative descriptive approach. The type of research used was the type of experimental research conducted with four meetings using coastal media. The subjects in this study were 11 children in Wali Urban Village, aged 4-5 years. Data collection was carried out by observation. The data analysis technique used in this study was the qualitative descriptive analysis technique. The results of the study showed that the symbolic thinking abilty of children aged 4-5 years using coastal media developed as expected.